Improvement of Mother’s Knowledge to Common 65s`Cold Treatment in Children Using Leaflet Through CBIA Method In Tamansari Village - Yulia Pratiwi; Evitri Yuliana Rahayu; Mera Putri Pratitis; Wildayanti Wildayanti; Aprillia Puspitasari Tunggadewi (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
The common cold is a frequently occurring disease in children. An approach to control the disease is through health education using the Cara Belajar Ibu Aktif (CBIA) method alongside a leaflet media. Family knowledge, particularly that of the mother, plays a crucial role in preventing the transmission of the common cold in children. Knowledge is formed as a result of new understanding. This study used quantitative quasi-experimental design with a one-group pretest–posttest approach. The study population consisted of mothers in Tamansari Village, Tlogowungu Subdistrict, Pati Regency. Samples were selected using simple random sampling based on predefined inclusion and exclusion criteria. Data were collected door-to-door using structured questionnaires administered before and after the educational intervention. The results showed that maternal knowledge was generally poor before the intervention. Following the CBIA-based health education, maternal knowledge significantly improved. The proportion of mothers with good knowledge increased from 58.6% to 73.7%, while the proportion with poor knowledge decreased from 32.3% to 9.0% Statistical analysis using Wilcoxon Signed-Rank Test revealed a significant difference in maternal knowledge before and after the intervention (p = 0.000 < 0.05). Health education using the CBIA method supported by leaflet media is an effective approach for improving maternal knowledge regarding the treatment of the common cold in children.